Luminescence energy yields of organic solid materials exited by photons of light or gamma-radiation - Tarasenko, O.A.; Galunov, N.Z.; Panikarskaya, V.D.; Sanin, E.V.; Tarasov, V.A.; Volkov, V.L. (Functional Materials, 2012)
In this paper we compare the energy yields both for the case of excitation by light photons of the visible range and for the excitation by gamma radiation for some organic scintillation crystals and polystyrene plastic scintillator. In the first case the energy of excitation is lower than the ionization potential of molecules, and in the second one the energy of excitation is higher than the ionization potential of molecules. It has been obtained that the energy yield in the case of excitation by photons of gamma radiation Yy is in the range from 0.018 to 0.056. These values are an order of magnitude smaller than the energy yield Yf obtained for photoexcitation.